Evidence-Based Practice in Primary Care Occupational Therapy: A Cross-Sectional Survey in Sweden - Ann-Charlotte Lindström; Susanne Bernhardsson (Occupational Therapy International)
Introduction. Understanding of attitudes, knowledge, and behaviour related to evidence-based practice (EBP) and guidelines in Swedish occupational therapy is limited. The study aims were to investigate attitudes, knowledge, and behaviour related to evidence-based practice and guidelines of Swedish occupational therapists in primary care. Methods. A web-based survey of 94 Swedish primary care occupational therapists (response rate 53.7%). Data were analysed using logistic regressions. Results. Attitudes towards EBP and guidelines were highly positive (97%–98%). About half of the respondents reported confidence in finding and using evidence. Almost two-thirds reported being aware of guidelines and 47% knowing where to find guidelines. Four-fifths stated that they had easy access to guidelines and 75% that they used guidelines frequently. Men were more likely to feel confident to find research (OR 8.58, 95% CI 1.03 to 71.66; p=0.047) and have easy access to guidelines (OR 9.10, 95% CI 1.94 to 42.83; p=0.005). Occupational therapists older than 50 years were more likely to integrate patient preferences with guideline use (OR 6.44, 95% CI 1.14 to 36.57; p=0.035). Few reported reading scientific articles, and many expressed uncertainty in finding research. The main barrier for using guidelines was reported to be lack of time. Conclusion. Although attitudes among primary care occupational therapists towards EBP are positive and a large proportion report using guidelines, many state that they want to learn more and improve their evidence-based practice skills. The findings suggest that education measures need to be taken to address the identified shortcomings.